The Silent Diffusion of Sticky Costs in the HoReCa Industry - Wolfram Irsa (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Sticky costs materialize when costs increase more with rising an activity than they decrease with falling of the very same amount of the activity. Over time a silent diffusion of sticky costs can be observed in the HoReCa (HOtel/REstaurant/CAtering) industry. In sticky costs literature the cost behaviour is evaluated by correlating the current growth in Selling, General and Administrative costs – often referred to overhead - with current revenue growth. Recently, research identified several attributes affecting the hysteresis (Greek: remaining even if the cause is no longer there) of cost. Managerial oversight, external regulatory conditions and company culture are an example of such attributes. First insights indicate that the dependence of a system on its history is the driving force to determine the severance of cost stickiness. It depends for different sizes of corporations on the corporate governance model and on the successful variabilization of costs. This paper presents the most important attributes affecting sticky cost. Further, the various implementations in real managerial decision-making processes in the HoReCa industry are described on the example of the region of Opatija, Croatia. A qualitative research using ATLAS.ti as Computer Assisted Qualitative Data Analysis Software (CAQDAS) is the chosen approach for unveiling the desired findings.
Keywords: D22; G41; M14; 330; cost behaviour; overhead cost management; qualitative research; VUCA (volatility; uncertainty; complexity and ambiguity)